Public initiatives to support entrepreneurs: Credit guarantees versus co-funding - Arping, Stefan; Lóránth, Gyöngyi; Morrison, Alan D. (Journal of Financial Stability, 2010)
We analyze financial support for the entrepreneurial sector. State support can raise welfare by relaxing financial constraints, but it can also reduce lending standards if entrepreneurs substitute public sources of collateral for their own assets, if it encourages excessive entrepreneurial entry, or if it undermines bank monitoring incentives. We derive a “pecking order” for support schemes: support funds should be channeled first to credit guarantee schemes and then, when entrepreneurs start to substitute public for private collateral, to co-funding entrepreneurial projects. The optimal level of credit guarantee is diminishing in the costs of incentivising bank monitoring. We show in an extension that the long-term effect of public subsidies may be to impair the private sector’s initiative to uncover cost savings.